Body Fat Percentage and Nutritional Status with Hs-CRP Levels in Hyperlipidemic Individuals - Azizah, Anisah Nimah; Marliyati, Sri Anna; Riyadi, Hadi (Sarana Ilmu Indonesia (salnesia), 2024)
cardiovascular disease and other metabolic disorders. High levels of C-reactive protein (hs-CRP) are commonly used to gauge cardiovascular risk, as elevated hs-CRP is linked with increased heart disease and chronic inflammation. This study examines how body fat percentage and nutritional status affect hs-CRP levels in individuals with hyperlipidemia. It involved 30 participants from a study at the SEAFAST Center IPB, where they were treated with high antioxidant and anti-inflammatory drinks for 4 weeks. Body fat percentage was measured via Bioelectrical Impedance Analysis (BIA), nutritional status was evaluated through clinical assessments of weight and height, and hs-CRP levels were assessed using ELISA immunoassay. The Chi-square test revealed significant relationships between both body fat percentage (X²=0,043, p-value<0,05) and nutritional status (X² = 0,05, p-value<0,05) with hs-CRP levels. These results suggest that both body fat percentage and nutritional status significantly impact hs-CRP levels in individuals with hyperlipidemia. Effective management of body fat and nutritional status could help reduce inflammation and cardiovascular risk in this population. This study supports the need for targeted interventions to better manage cardiovascular health in individuals with hyperlipidemia.